Effect of epoxidized natural rubber compatibilizer on porous natural rubber foam properties: Chemical crosslinks, elasticity, weathering and sound absorption behaviors - Kriengsak Damampai; Kanoknan Boonpan; Yeampon Nakaramontri (eXPRESS Polymer Letters, 2025)
This study investigated the properties of the natural rubber (NR) foam filled with azodicarbonamide (ADC) blowing agents by combination to various ratios of epoxidized NR (ENR) for flexible foam applications. Compound operation was prepared with an open two-roll mill and the production was fabricated by compression molding. The study elucidated properties related to crosslinking behaviors, mechanical and dynamic properties, elasticity, abrasion, weathering resistance, and sound absorption efficiency. The ENR and ADC concentrations affected the tensile testing and also the durability properties of the NR/ENR. The NR and ENR foam of 60/40 filled with 10 phr of ADC demonstrated good properties across various parameters, showing acceptable tensile properties, abrasion resistance, and QVA light resistance. Additionally, the presence of a closed-cell structure in the blends reduced crack propagation in the NR matrix during aging, improving weathering resistance. The absorption coefficient increased with higher ADC content, being optimal at 15 phr, due to the lower density and higher porosity of the opened-cell material, which enhances its ability to interact more effectively with incoming energy at 1600 and 6400 Hz. The findings encourage the use of ENR for blending in NR for improved ENR and ADC concentrations since dipole-dipole interaction from ENR-ADC caused ADC dispersability, providing complexed foam structures for force expansion and aslo sound wave absorption.